PEMBERIAN PUPUK KALIUM DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Qolby, Ayu Nurul Aini; Murniati, Murniati; Armaini, Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to know the effect of K fertilizer and POC concentration, and to get the best combination between K fertilizer and POC concentration for the growth and production of shallot plant (Allium ascalonicum L.). This research was conducted in experimental field of Faculty of Agriculture, University of Riau, Pekanbaru. The study was conducted for three months, from February to April 2017. The experiment was conducted experimentally in the field using factorial CRD, consisting of two factors and 3 replications. The first factor is potassium fertilizer (KCl): K1: 300 kg.ha-1, K2: 400 kg.ha-1, K3: 500 kg.ha-1. The second factor is POC concentration: P0: 1 ml.l-1, P1: 3 ml.l-1, P2: 6 ml.l-1. Parameters observed in this study were: number of leaves (sheet), plant height (cm), harvest age (dap), number of tubers (fruit), tuber (cm), fresh weight of tubers (g.ha-1) and bulbs dry weight (g.ha-1). The test results were further tested using Duncan's multiple-range test at a 5% level. The results showed that the combination of KCl 500 kg.ha-1 and POC 6 ml.l-1 were the best doses in increasing plant height, tuber count, tuber bulbs, fresh weight of tubers and bulbs dry weight. Keywords: Potassium fertilizer, POC, shallot